Pengaruh Pengungkapan Corporate Social Responsibility dan Kinerja Lingkungan terhadap Harga Saham: (Studi Empiris pada Perusahaan yang terdaftar dalam BEI Periode 2018-2021) - Rovishany, Nabila Daffa; Gunawan, Arwan; Sudradjat, Sudradjat; Ishak, Jouzar Farouq (Indonesian Accounting Literacy Journal, 2025)
Nowadays, financial information that only includes profit is not enough to ensure the continuity of the company. Companies need to provide other information needed by stakeholders in terms of decision making, namely information on social and environmental aspects that are realized by implementing corporate social responsibility. This study aims to determine the effect of CSR-economic, CSR-environmental, CSR-social, and environmental performance disclosures on the stock prices of companies listed in the LQ45 Index. The research sample consisted of 11 companies selected through several criteria with a period of 4 years (2018-2021). This study uses a quantitative method using secondary data obtained from annual reports and sustainability reports. The hypothesis was tested using multiple linear regression analysis. The results showed that CSR-economic had a negative and significant effect on stock prices, CSR-environment had a positive and significant effect on stock prices, while CSR-social and environmental performance had no effect on stock prices.